Nanotechnology: A Promising Targeted Drug Delivery System for Brain Tumours and Alzheimer's Disease - Unnisa, Aziz; Greig, Nigel H.; Kamal, Mohammad A. (Current Medicinal Chemistry, 2023)
Nanotechnology is the process of modulating shape and size at the nanoscale to design and manufacture structures, devices, and systems. Nanotechnology's prospective breakthroughs are incredible, and some cannot even be comprehended right now. The blood-brain barrier, which is a prominent physiological barrier in the brain, limits the adequate elimination of malignant cells by changing the concentration of therapeutic agents at the target tissue. Nanotechnology has sparked interest in recent years as a way to solve these issues and improve drug delivery. Inorganic and organic nanomaterials have been found to be beneficial for bioimaging approaches and controlled drug delivery systems. Brain cancer (BC) and Alzheimer’s disease (AD) are two of the prominent disorders of the brain. Even though the pathophysiology and pathways for both disorders are different, nanotechnology with common features can deliver drugs over the BBB, advancing the treatment of both disorders. This innovative technology could provide a foundation for combining diagnostics, treatments, and delivery of targeted drugs to the tumour site, further supervising the response and designing and delivering materials by employing atomic and molecular elements. There is currently limited treatment for Alzheimer's disease, and reversing further progression is difficult. Recently, various nanocarriers have been investigated to improve the bioavailability and efficacy of many AD treatment drugs. Nanotechnology-assisted drugs can penetrate the BBB and reach the target tissue. However, further research is required in this field to ensure the safety and efficacy of drug-loaded nanoparticles. The application of nanotechnology in the diagnosis and treatment of brain tumours and Alzheimer's disease is briefly discussed in this review.
Keywords: nanoparticles